2008
DOI: 10.1080/07357900802087275
|View full text |Cite
|
Sign up to set email alerts
|

RAS: Target for Cancer Therapy

Abstract: The RAS protein controls signaling pathway are major player in cell growth, its regulation and malignant transformation. Any activation in RAS brings alteration in upstream or downstream signaling component. Activating mutation in RAS is found in approximately 30% of human cancer. RAS plays essential role in tumor maintenance and is therefore an appropriate target for anticancer therapy. Among the anti-RAS strategies that are under evaluation in the clinic are pharmacologic inhibitors designed to prevent: (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 52 publications
2
61
0
Order By: Relevance
“…We found that colorectal cancer cell lines were also highly susceptible to IGFBP7-mediated apoptosis, consistent with the high frequency of activating BRAF or RAS mutations, and presumably increased BRAF-MEK-ERK signaling, in colorectal cancers (1,9). Significantly, previous studies have found that IGFBP7 expression is lost in human colorectal cancers (17,18), consistent with the possibility that IGFBP7 is a colorectal cancer tumor suppressor (19,20).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…We found that colorectal cancer cell lines were also highly susceptible to IGFBP7-mediated apoptosis, consistent with the high frequency of activating BRAF or RAS mutations, and presumably increased BRAF-MEK-ERK signaling, in colorectal cancers (1,9). Significantly, previous studies have found that IGFBP7 expression is lost in human colorectal cancers (17,18), consistent with the possibility that IGFBP7 is a colorectal cancer tumor suppressor (19,20).…”
Section: Discussionsupporting
confidence: 68%
“…In addition, up to 30% of solid tumors contain activating RAS mutations, which can also increase BRAF-MEK-ERK signaling (reviewed in ref. 9). We therefore investigated the potential use of IGFBP7 in the treatment of other cancers.…”
Section: Susceptibility Of Nci60 Human Cancer Cell Lines To Igfbp7 Trmentioning
confidence: 99%
“…A total of 3 × 10 6 A549, H460, HCT116, or MDAMB231 cells were injected s.c. into the flank region of 6-wk-old female athymic mice (Janvier). When tumors reached 50 mm 3 , the mice were randomized into four groups (n = 7/group) for the following treatment: vehicle, RAF265 (12 mg/kg daily), RAD001 (12 mg/kg daily), or both. All drug were administered over 14 d (6 d on, 2 d off, 6 d on), and the drug combination was administered concurrently.…”
Section: In Vivo Experimentsmentioning
confidence: 99%
“…Different pharmacologic strategies have been developed to inhibit KRAS oncogenic activation, including inhibition of its association with the plasma membrane (prenylation and postprenylation inhibitors), downstream signaling (kinase inhibitor), upstream pathways (kinase inhibitor and monoclonal antibody), and protein expression of RAS or other components of the pathway (small interfering RNA and antisense oligonucleotides; ref. 3). However, several of these therapeutic agents have yielded disappointing results (4).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, identification of genes or molecular pathways that are responsible for the development and progression of breast cancer with understanding of their clinical significance are necessary, and may aid in the development of novel approaches for the effective treatment and prognostic prediction of breast cancer. Towards this end, our study focused on Ras GTPase-activating protein 1 (RASA1), which functions to inactivate Ras-GTPase and inhibit mitogenic signaling to downstream protein partners through its N-terminal SH2-SH3-SH2 domains (4)(5)(6). Aberrant expression of RASA1 protein occurs in ~30% of all human cancers, including breast cancer, but in up to 90% of pancreatic cancers (7).…”
Section: Introductionmentioning
confidence: 99%